Trigeminal Neuralgia: Indications of Gasserian Ganglion Gompression with Balloon Catheter in the Modern Era - Mario Francesco Fraioli; Andrea Pagano; Chiara Fraioli; Pierpaolo Lunardi (International Journal of Pain Management, 2019)
Many therapies are available for trigeminal neuralgia (TN), from medical therapy to invasive, mininvasive and non-invasive methods. There is no a unique indication concerning the choice of treatment; we report our indications for gasserian ganglion compression with balloon by percutaneous approach. Out of 421 patients affected by TN treated with various methods from 2004 through to 2014, we present 46 patients treated by gasserian ganglion compression with balloon catheter. Patients selected for this procedure were only those refractory to medical therapy and refractory to the other available therapies (radiofrequency, microvascular decompression, radiosurgery, glycerolization, peripheral alcoholizations): balloon compression was performed as third line therapy. After the procedure, twenty-eight patients were classified as BNI pain intensity score grade 1, seven other as grade 2, three other as grade 3, six were classified as BNI grade 4, and in one patient no improvement of pain occurred (BNI grade 5). After an average period of follow up of 8,6 years, four cases of pain recurrence occurred. Because balloon compression is an ablative and non-selective procedure and all three trigeminal divisions are damaged to achieve stable pain remission, the procedure was performed only in patients affected by recurrent TN refractory to the other available methods.
Keywords: trigeminal neuralgia